2021
DOI: 10.2147/dnnd.s340117
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Major Histocompatibility Complex (MHC) Class-I Expression in Different Neuromuscular Diseases

Abstract: Background Major histocompatibility complex (MHC) class-1 antigen is a glycoprotein expressed in all nucleated cells. The aim of this study was to assess MHC class-I expression in different neuromuscular diseases. Methods The authors reviewed the data of 54 patients with neuromuscular diseases. Anti MHC class-I antibody was performed on the frozen muscle tissues using immunohistochemistry. MHC class-I was scored based on its expression on muscle fibers (0: normal, 1: ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Among these, the inflammatory marker detected in all 5 cases was an increase in MHC-I on the sarcolemma of muscle fibres. Elevated MHC-I in muscle fibres is a highly sensitive indicator for myopathy (19,20). MHC-I usually participates in the antigen presentation process and is generally underexpressed in the sarcoplasm (21), while it is expressed only in endomysial capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the inflammatory marker detected in all 5 cases was an increase in MHC-I on the sarcolemma of muscle fibres. Elevated MHC-I in muscle fibres is a highly sensitive indicator for myopathy (19,20). MHC-I usually participates in the antigen presentation process and is generally underexpressed in the sarcoplasm (21), while it is expressed only in endomysial capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…We are mindful that MHC I expression is not wholly restricted to myositis and that analysis of biopsies from a range of muscular dystrophies, also report significant sarco‐capillary expression of MHC I. 50 …”
Section: Discussionmentioning
confidence: 99%
“…Even though our findings provide the foundation for the role of MHC I‐mediated myokine release, further experiments on patient‐derived cells are needed to contextualize these findings. We are mindful that MHC I expression is not wholly restricted to myositis and that analysis of biopsies from a range of muscular dystrophies, also report significant sarco‐capillary expression of MHC I 50 …”
Section: Discussionmentioning
confidence: 99%
“…Despite these, the literature has not explained the origin of muscle fiber damage or muscle weakness ( 136 ). To date, the most well-described example is upregulation of the expression of MHC-I in myofibers (sarcolemma surface), whose expression is not usual in normal muscle tissue (endomysial capillaries), thus stimulating the activation of ER stress responses such as an accumulation of misfolded glycoproteins and the activation of NF-κB, causing an inflammatory response via IRE1, tumor necrosis factor (TNF)-α, and TRAF2 ( 137 , 138 ). It has been demonstrated that BiP/GRP78, CRT, and heat shock protein 90-α2 expression levels are augmented according to intermediate or high MHC-I expression in myositis muscle ( 139 ).…”
Section: Non-immunopathological Mechanismsmentioning
confidence: 99%